PERAN PENGGUNAAN MEDIA SOSIAL TERHADAP LOYALITAS PELANGGAN DIMEDIASI KEPERCAYAAN PELANGGAN DAN KUALITAS INFORMASI - Senjaliani, Verrent; Suwarno, Henky Lisan Suwarno (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2024)
Currently, millennials have the highest expenditure in the fashion industry. There are several fashion brands that are often used by the Indonesian community, especially the Uniqlo brand, which is favored by Indonesians at the moment. The purpose of this research is to examine and analyze the role of social media usage on customer loyalty, mediated by customer trust and information quality, on a sample of Uniqlo consumers who seek product information through social media. This type of research is causal explanatory, with data collection using survey techniques and a questionnaire method with a total of 200 respondents and the help of SPLS. The results of this study indicate that the role of trust has a positive influence while information quality does not have a positive influence in mediating the effect of social media usage on customer loyalty.